2017
DOI: 10.1073/pnas.1704835114
|View full text |Cite
|
Sign up to set email alerts
|

Drk-mediated signaling to Rho kinase is required for anesthesia-resistant memory in Drosophila

Abstract: Significance Anesthesia-resistant memory (ARM) has been puzzling because unlike long-term memory (LTM), it is translation independent in Drosophila . Although the two forms of consolidated memory are housed within the mushroom body neurons, they seem to employ distinct molecular pathways, with those that underlie ARM largely unknown. Elucidation of these pathways is essential to understanding ARM, how it differs from LTM, and what underlies their apparent inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The interaction of RADISH and BRUCHPILOT at the synaptic active zone has been proposed to regulate neurotransmitter release[17], and genetic knockdown of radish or bruchpilot in αβ neurons disrupts ARM[17, 20]. A recent study indicated that Drk–Drok signaling is essential for ARM formation in αβ neurons, and related to dynamic cytoskeletal changes[33]. In addition, the dopamine type 2 (D2R) and serotonin (5HT1A) receptors in αβ neurons are also critical for ARM formation[34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of RADISH and BRUCHPILOT at the synaptic active zone has been proposed to regulate neurotransmitter release[17], and genetic knockdown of radish or bruchpilot in αβ neurons disrupts ARM[17, 20]. A recent study indicated that Drk–Drok signaling is essential for ARM formation in αβ neurons, and related to dynamic cytoskeletal changes[33]. In addition, the dopamine type 2 (D2R) and serotonin (5HT1A) receptors in αβ neurons are also critical for ARM formation[34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…The MEF2 MB lobe expression pattern expression gives clues to possible transcriptional interactors for MEF2. Examples of MB markers with similar Kenyon cell subtype distribution to MEF2 include FOXP ( DasGupta et al, 2014 ), HDAC4 ( Fitzsimons et al, 2013 ), DRK ( Crittenden et al, 1998 ; Kotoula et al, 2017 ), and FASII ( Crittenden et al, 1998 ; Cheng et al, 2001 ). MEF2 interactions with several of these molecules have already been established.…”
Section: Discussionmentioning
confidence: 99%
“…Flies were dissected in cold PBS, fixed in 4% paraformaldehyde for 15 min, and imaged by laser-scanning confocal microscopy (TCS SP8, Leica). F-actin levels were determined in adult fly brains from three independent experiments as described previously (Fulga et al, 2007;Kotoula et al, 2017).…”
Section: Methodsmentioning
confidence: 99%